Hermetic Packaging Based on Cu–Sn and Au–Au Dual Bonding for High-Temperature Graphene Pressure Sensor - Junqiang Wang; Haikun Zhang; Xuwen Chen; Mengwei Li (Micromachines, 2022)
A chip-level hermetic package for a high-temperature graphene pressure sensor was investigated. The silicon cap, chip and substrate were stacked by Cu–Sn and Au–Au bonding to enable wide-range measurements while guaranteeing a high hermetic package. Prior to bonding, the sample was treated with Ar (5% H2) plasma. The Cu–Sn bonding was firstly performed at 260 °C for 15 min with a pressure of 9.9 MPa, and the corresponding process conditions for Au–Au bonding has increased to 300 °C, 20 min and 19.8 MPa respectively. The average shearing strength was 14.3 MPa, and an excellent leak rate of 1.72 × 10−4 Pa·cm3/s was also achieved. After high-temperature storage (HTS) at 350 °C for 10 h, the resistance of graphene decreased slightly because the dual bonding provided oxygen-free environment for graphene. The leakage rate of the device slightly increased to 2.1 × 10−4 Pa·cm3/s, and the average shear strength just decreased to 13.5 MPa. Finally, under the pressure range of 0–100 MPa, the graphene pressure sensor exhibited a high average sensitivity of 3.11 Ω/MPa. In conclusion, the dual bonding that combined Cu–Sn and Au–Au is extremely suitable for hermetic packaging in high-temperature graphene pressure sensors.